Molecular simulation of C60 adsorption onto a TiO2 rutile (110) surface - Carvalho, A.J. Palace (2012)
Monte Carlo molecular simulation study is presented on the adsorption and growth of C60 films on the surface of the (1 1 0) face of rutile. Simulations are performed for a temperature of 600 K using atomistic models both for the fullerene molecules and the TiO2 surface. It is found in this work that C60 is adsorbed preferably in an ordered arrangement along the surface depressions over the exposed undercoordinated Ti cations. At low densities adsorption occurs preferably at alternate rows, with locations in consecutive rows being occupied appreciably only at higher C60 densities. At low densities, the fullerene molecules tend to aggregate into islands in the surface plane. Additional layers of C60 form only as the density increases, and do so before a monolayer is completed in all consecutive rows. Full monolayer capacity obtained at the highest densities is about 0.9 C60 molecules per nm2, but this is only achieved by completing the packing of molecules in interstices at a slightly upper level. The fraction of the molecules that lie closest to the surface only amounts to 0.6 molecules per nm2.